Asymptotic Properties Of Ordinal Statistics (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
The asymptotic theory of ordinal statistics deals with the distribution of appropriately normalized (and centered) quantities Crn: at n →¥. At the first stage, it is usually assumed that Crn: is the rth ordinal statistic in a random sample of volume n from a distribution with a distribution function R( x) . However, as we will see later, many types of dependence between , ,..., C C C 1 2, n . Cp do not violate the type of marginal distributions.